Akibat Hukum Praktik Perkawinan yang Tidak Tercatat di Kantor Catatan Sipil Dikaitkan dengan Hak Waris Anak di Luar Perkawinan Menurut Kajian Hukum Perdata - Rian T R Simanjuntak; Fariz Aditya; Iwain O. Nababan; Tawarika M. Pandiangan; Eka Putriani Sihombing; Rahmi Siregar; Parlaungan Gabriel Siahaan; Sri Hadiningrum (Departement of Mathematics Education, 2024)
Referring to the Constitutional Court decision Number 46 / PUU-VIII/2010 that recognizes illegitimate children as having a civil relationship with their biological father, so that illegitimate children have inheritance rights. This decision has drawn pros and cons from the public. For those who support it, this decision is seen as legal protection and justice for illegitimate children, whereas for those who reject it, this decision is seen as an opening for crimes of deviation from religious values, such as unregistered marriages, acts of adultery or sexual immorality. This research method is empirical juridical. Types of secondary data sources obtained using library research. The results of the research show that to obtain legal certainty, the heir's statement should include the names of children from unregistered marriages, but this cannot be done, because there are no statutory regulations that determine the names of children resulting from extramarital marriages. is included in the deed, so an inheritance certificate containing the name of a child resulting from an unregistered marriage has legal force, therefore it is recommended that the government immediately do this and make regulations regarding the creation of inheritance certificates for children resulting from an unregistered marriage, so that it has clear legal force and permanent, and binding in general.